2009
DOI: 10.1007/978-3-642-03655-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Can You Be Persuaded? Individual Differences in Susceptibility to Persuasion

Abstract: Persuasive technologies are growing in popularity and many designers create systems which intentionally change users attitudes or behaviors. This study shows that peoples individual differences in susceptibility to persuasion, as implemented using the six persuasion principles proposed by Cialdini 2, relates to their compliance to a persuasive request which is accompanied by a persuasive cue. This result is a starting point for designers to start incorporating individual differences in susceptibility to persua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 3 publications
0
81
0
1
Order By: Relevance
“…eoretical and empirical studies have suggested di erent factors for persuasive technology personalization [46,51] [34,45,47], and • Individual susceptibility to persuasive a empts [31,32,50].…”
Section: Personalized Gami Cationmentioning
confidence: 99%
“…eoretical and empirical studies have suggested di erent factors for persuasive technology personalization [46,51] [34,45,47], and • Individual susceptibility to persuasive a empts [31,32,50].…”
Section: Personalized Gami Cationmentioning
confidence: 99%
“…Cialdini (2001) distinguished six persuasion strategies which can be applied to change behavior of people. These strategies have been used to change human behavior in different contexts; such as in online commerce, fund-raising, advertisements, and health information systems (Cialdini, 1993(Cialdini, , 2001Cialdini & Goldstein, 2002;Kaptein, Markopoulos, de Ruyter, & Aarts, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Another foreseen synergy between persuasive systems for sustainable mobility and social networks consists in the possibility of automatically retrieving user profile data on preferences and needs that could be used to provide more tailored travel options and appropriate motivational interventions. Moreover, previous work has shown significant individual differences in user's responses to influence attempts (Cialdini, Trost, & Newsom, 1995;Guadagno, Asher, Demaine, & Cialdini, 2001;Kaptein, Markopoulos, de Ruyter, & Aarts, 2009) and that people desire to act consistently with their attitudes and beliefs (Guadagno & Cialdini, 2010). This suggests the relevance of systems that adapt to these differences by utilizing persuasion profiles: estimates of an individual user's susceptibility to different influence strategies should be considered (Kaptein & Eckles, 2010).…”
Section: Lessons Learntmentioning
confidence: 95%